Practical training of nurses and midwives within the project “The Modern University – Cooperation” – the students’ opinions - Stadnicka, Grażyna; Kocka, Katarzyna; Nazaruk-Napora, Marta; Jarczyk, Jarczyk (Nursing in the 21st Century, 2012)
PRACTICAL TRAINING OF NURSES AND MIDWIVES WITHIN THE PROJECT “THE MODERN UNIVERSITY – COOPERATION” – THE STUDENTS’ OPINIONS Introduction. The practical training programme is aimed at preparing nursing/midwifery students to perform their profession. Aim. The objective of the study was to present the students’ opinions on practical training carried out during the 3rd year of studies within the project "The Modern University – Cooperation”. Material and methodology. The survey was conducted among 3rd year students of nursing and midwifery with the application of the panel method, using the auditorium questionnaire. The results were subject to a statistical analysis involving the Chi-square test, Mann-Whitney U test. Results. Most of the surveyed students of nursing and midwifery claim that there is a demand for nurses/midwives in the labour market – (71.17%; 72.00%, respectively). In a 10-point scale (1 – the lowest rating, 10 – the highest rating), the surveyed students of nursing evaluated the satisfaction from their major at the level of 7.15; the students of midwifery assigned to their major 7.83 points. The respondents also confirm the assumption that the participation in the project “The Modern University – Cooperation” is important in improving the professional skills - nursing – 87.38 %, midwifery – 92.00%. The practical training programme meets the expectations of 68.0% of the surveyed midwifery students, and of 54.96% of nursing students. Conclusions. The practical training programme of nursing/midwifery at Bachelor’s level meets the expectations of most students in the area of preparing them for performing their professional roles.